Co-viewing Experience in Video Websites: The Effect of Social Presence on E-Loyalty. Issue 3 (3rd July 2018) - Fang, Jiaming; Chen, Lei; Wen, Chao; Prybutok, Victor R.
ABSTRACT: Video website operators work in a highly competitive market and, thus, cultivating evangelists who keep coming back and spreading positive word-of-mouth (WOM) referrals is important to retain market share and boost sustainability. This study empirically tests a model proposing that social presence elicited by the emerging bullet screen ("DanMu" in Chinese or "Danmaku" in Japanese) system in video websites serially affects immersive experience and perceived benefits, which in turn influence viewers' e-loyalty. Data collected from 523 participants provide strong support for the proposed model. The results indicate that compelling immersive experience and perceived benefits are important mediators explaining the theoretical mechanism of how social presence affects loyalty. The presence of moderators such as group identification reinforces the influence of social presence on immersion. In addition, this study also suggests that perceived benefits differentially affect the two facets of e-loyalty (i.e., revisit intention and positive WOM). Specifically, revisit intention is mainly driven by the perceived hedonic benefit while positive WOM likelihood is largely determined by the utilitarian and social benefits. This study is the first to provide theoretical insights into understanding how increased social presence triggered by DanMu comments inspires the desired e-loyalty responses.